2008
DOI: 10.1002/cjce.5450830310
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition Determination at the Bottom Region of a Recovery Boiler Furnace by Direct Minimization of Gibbs Free Energy

Abstract: An optimization strategy has been applied to describe the chemical composition at the furnace bottom in the Kraft recovery boiler of a pulp production process. The concentrations of each involved chemical species were calculated through an optimization approach, minimizing the Gibbs free energy of the system. Various systems were proposed and tested, assuming different chemical species and phases number. Because serious initialization problems were found at this stage for some of the proposed systems, an optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(10 reference statements)
1
2
0
3
Order By: Relevance
“…Table 6 (test 1 to 7). The model reproduces the behavior reported in literature and that is expected for the system (Costa et al, 2005;Adams, 1997;Grace, 1992). Na 2 CO 3 and Na 2 S are the principal chemical species of the obtained smelt (condensed phase) as reported by Adams (1997) and Grace (1992).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Table 6 (test 1 to 7). The model reproduces the behavior reported in literature and that is expected for the system (Costa et al, 2005;Adams, 1997;Grace, 1992). Na 2 CO 3 and Na 2 S are the principal chemical species of the obtained smelt (condensed phase) as reported by Adams (1997) and Grace (1992).…”
Section: Resultssupporting
confidence: 85%
“…Grace (1992) affirms that the furnace bottom of the recovery boiler is poor in oxygen and this information is shown in Table 6. Costa et al (2005) studied a different recovery boiler and reported that the increase of black liquor feed promotes an increase of the reduction efficiency since the oxygen concentration is fixed. This behavior is observed in Table 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na literatura diversas pesquisas usam esta metodologia para predizer a composição de sistemas com muitas espécies e diversas fases em equilíbrio químico [9][10][11][12][13][14]. A energia de Gibbs total de um sistema fechado, à temperatura e a pressão constantes, diminui durante um processo irreversível e a condição de equilíbrio é atingida quando a energia de Gibbs alcança seu valor mínimo [15].…”
Section: Metodologia Da Minimização Da Energia Livre De Gibbsunclassified
“…[18][19][20][21][22] Diante dessas informações, o presente trabalho teve como objetivo a investigação do comportamento viscoelástico de amostras de licor negro de madeira de eucalipto (hardwood), resultantes do processo Kraft na Celulose Nipo Brasileira -CENIBRA, localizada no município de Belo Oriente-MG. As amostras foram coletadas nos seguintes estágios do processo Kraft: 1) após a estação de evaporação 2 de múltiplos efeitos -EVA2 (licor negro sem cinzas -LNSC), e 2) após tanques de reciclagem de cinzas de caldeira, nas vizinhanças da caldeira de recuperação 3 -RB3 (denominada licor negro com cinzas -LNCC); ambos com concentrações de sólidos da ordem de 70%, comum para amostras de LN. 23,24 Tais amostras foram escolhidas afim de se realizar um estudo comparativo.…”
Section: Introductionunclassified